MANAJEMEN LATIHAN KETERAMPILAN DAN KEPEMIMPINAN PEMUDA DENGAN SISTEM PENDEKATAN DESA BAHAGIA DAMPAKNYA TERHADAP KETELADANAN - Arif Budiman, Fajar; Dudi Darmawan, Eki (LPPM Politeknik Pajajaran ICB, 2022)
The implementation of education and training is a series of activities to control continuous educational activities so that they are effective in achieving the goals of education and training. This research focused on Youth Skills and Leadership Training (LKKP) for members of the Bandung City Flag Raising Troop (PASKIBRA) using the Happy Village Approach System. The purpose of this study was to analyze and describe the management of Youth Skills and Leadership Training for PASKIBRA Bandung City members using the Happy Village System Approach and the impact of this training on exemplary students of PASKIBRA Bandung City members. Data collection was carried out using observation, interviews, and documentation instruments. The results showed that Youth Management and Leadership Skills Training with the Happy Village System Approach for Paskibra Bandung members was generally successful in increasing the exemplary behavior of Paskibra Bandung students both in family life and at school.